Military Accessories from the “Tursko Castle” Near Połaniec, Świętokrzyskie Voivodeship. A Contribution to Research on Mongolian and Mongolian-Ruthenian Raids on the Sandomierz Lands in the 13th Century - Florek, Marek (The University of Rzeszów Publishing House, 2024)
The so-called Tursko Castle near Połaniec is the remnants of earth fortifications from the 17th century erected around an evangelical church. At the end of the 19th century it began to be associated with the Battle of Tursko, which took place during the first Mongolian raid in 1241. It was believed to be remains of a castle or stronghold located near the site of the battle, or the remnants of a Mongolian camp. At that time, no one knew where the clash had taken place. During a search for artefacts conducted within the perimeter of the castle in 2022–2023, a series of medieval military accessories were discovered. They included 12 tanged arrowheads and a fragment of a mace head. These artefacts should be associated with thirteenth-century Mongolian and Mongolian-Ruthenian raids on the Sandomierz lands.
Keywords: Middle Ages; military accessories; raids; Sandomierz lands; Battle of Tursko